Caught in a vicious cycle? Student perceptions of academic dishonesty in the business classroom. Issue 3 (November 2022) - Lord Ferguson, Sarah; Flostrand, Andrew; Lam, Joey; Pitt, Leyland
Abstract: Academic dishonesty (AD) continues to threaten the integrity of post-secondary institutions around the world with new scandals publicized every year. While AD has received considerable research attention, most of these studies have focused on quantifying the characteristics of cheaters and cheating behaviour, primarily at the undergraduate level. In the present study, we used a mix-methods approach to explore student attitudes towards AD among business students at both graduate and undergraduate levels at a North American university. We found that the perceived prevalence of AD was higher among undergraduates, who regarded cheating scenarios to be less wrong when compared to graduates. When asked how AD impacted other students, the undergraduate respondents highlighted the consequences of artificially inflating the normalized grading distribution, while the graduate respondents focused on the erosion of cohort dynamics and professional networks. Both groups of students shared that they faced increasing competition and other pressures that motivated them to engage in AD. These factors propagated cheating behaviour through complex positive feedback loop mechanisms, which we termed the Vicious Cycles of Cheating. Based on these factors, we proposed recommendations that are directly informed by students and designed to break these cycles. Highlights: Perceived prevalence of cheating was higher among undergraduates than graduates. Undergraduates regarded cheating scenarios to be less wrong than graduates. Undergraduates described how cheating inflated normalized grading distributions. Graduates explained that cheating eroded cohort dynamics and professional networks. Cheating is perpetuated by feedback mechanisms at individual and systemic levels.